2018
DOI: 10.1136/ejhpharm-2017-001421
|View full text |Cite
|
Sign up to set email alerts
|

Palliative analgesia with topical sevoflurane in cancer-related skin ulcers: a case report

Abstract: A Caucasian 39-year-old male patient with a poorly-differentiated infiltrating epidermoid penile carcinoma with urethral invasion was diagnosed. The patient received concomitant adjuvant chemotherapy with radiotherapy in the palliative setting, which produced painful ulceration of tumour lesions at loco-regional level (Numerical Rate Scale, NRS=9). The patient consented for treatment with direct topical sevoflurane instillations, at initial doses of 1 mL/cm2 of ulcerated area, as per unit protocol. The local u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Sevoflurane application was followed by a remarkably fast analgesic effect, with 50% of patients allowing initiation of debridement after only 1 or 2 minutes. This quick analgesic effect is in line with previous reports with sevoflurane 9,13,[15][16][17][18][19][20][21][23][24][25][26][27][28] or even ether 29 and contrasts compellingly with the delay of 30-40 minutes needed for EMLA cream. 10 Therefore, sevoflurane seems a more convenient alternative than EMLA.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Sevoflurane application was followed by a remarkably fast analgesic effect, with 50% of patients allowing initiation of debridement after only 1 or 2 minutes. This quick analgesic effect is in line with previous reports with sevoflurane 9,13,[15][16][17][18][19][20][21][23][24][25][26][27][28] or even ether 29 and contrasts compellingly with the delay of 30-40 minutes needed for EMLA cream. 10 Therefore, sevoflurane seems a more convenient alternative than EMLA.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that sevoflurane produces a quick, intense, and long-lasting analgesic effect when it is irrigated on vascular chronic wounds of both venous 9,14-24 and ischemic 13 etiology, both for pain at rest 9,[13][14][15][16][17][18][19][20][21][22][23][24] and pain elicited by debridement. 13 Irruptive pain of neuropathic origin in chronic oncologic 15,25 and diabetic foot 26 wounds has been successfully controlled with sevoflurane, and the analgesic effect has also been described when treating infected postsurgical wounds. 27,28 The results of the present work confirm these analgesic properties for the specific case of acute wound pain caused by sharp debridement of vascular wounds as well as wounds of other etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a number of studies on the successful use of topical sevoflurane on vascular ischaemic ulcers has been published . In the same line, but conducted in a somewhat different setting, other authors have reported an improvement in pain scores after topical sevoflurane administration in patients with oncological ulcers, which was also associated with a decrease of opioid requirements . In all these studies, sevoflurane achieved rapid, intense, and durable pain relief.…”
Section: Discussionmentioning
confidence: 98%